Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Olimpiade Matematika di SMP Kristen Eben Haezar 2 Manado - Siska Daniaty Siahaan; Philotheus E. A. Tuerah; Victor R. Sulangi (Journal on Education, 2023)
The purpose of this research is to find out what types of errors students can make in solving mathematics Olympiad questions based on Newman's criteria and their causes. The method used by the author is a qualitative descriptive research method. The results of the research are: the errors made were the criteria for errors in understanding the questions (Comprehension Error), transformation errors (Transform Error), process skill errors (Process Skill) and errors in drawing conclusions (Encoding Error). The causes are: 1) lack of understanding or not understanding the meaning of the question. 2) not being careful in working on the questions. 3) don't understand how to process the information obtained from the questions. 4) students experience forgetting factors. 5) students cannot determine what formula to use in solving the problem. 6) don't know how to solve the existing problems. 7) less skilled in completing operations in mathematics. 8) rush. 9) students are lazy in solving existing problems and focus on solving other problems. 10) processing time has expired.